Are brand names special words? Letter visual‐similarity affects the identification of brand names, but not common words. - Perea, Manuel; Baciero, Ana; Labusch, Melanie; Fernández‐López, María; Marcet, Ana (British Journal of Psychology, 2022)
Brand names are often considered a special type of words of special relevance to examine the role of visual codes during reading: unlike common words, brand names are typically presented with the same letter‐case configuration (e.g., IKEA, adidas). Recently, Pathak et al. (European Journal of Marketing, 2019, 53, 2109) found an effect of visual similarity for misspelled brand names when the participants had to decide whether the brand name was spelled correctly or not (e.g., tacebook [baseword: facebook] was responded more slowly and less accurately than xacebook). This finding is at odds with both orthographically based visual‐word recognition models and prior experiments using misspelled common words (e.g., viotin [baseword: violin] is identified as fast as viocin). To solve this puzzle, we designed two experiments in which the participants had to decide whether the presented item was written correctly. In Experiment 1, following a procedure similar to Pathak et al. (European Journal of Marketing, 2019, 53, 2109), we examined the effect of visual similarity on misspelled brand names with/without graphical information (e.g., anazon vs. atazon [baseword: amazon]). Experiment 2 was parallel to Experiment 1, but we focused on misspelled common words (e.g., anarillo vs. atarillo; baseword: amarillo [yellow in Spanish]). Results showed a sizeable effect of visual similarity on misspelled brand names – regardless of their graphical information, but not on misspelled common words. These findings suggest that visual codes play a greater role when identifying brand names than common words. We examined how models of visual‐word recognition can account for this dissociation.